Pengaruh Metode Pembelajaran Fun Learning pada Mata Pelajaran Bahasa Inggris Materi Games and Sport Kelas 3 Sekolah Dasar - Azhara, Andita Amma; Setiyawan, Heri (Indo-MathEdu Intellectuals Journal, 2025)
This research explores the application of Fun Learning methods in primary education, aiming to analyze its impact on students' academic performance and learning motivation, especially in overcoming learning difficulties. Using qualitative descriptive methods, data were collected through in-depth interviews with teachers and students as well as the analysis of relevant documents such as lesson plans and evaluation results. The data analysis technique applied is thematic analysis, in which patterns, themes, and categories are extracted from qualitative data for comprehensive interpretation. The results indicate that Fun Learning, especially when integrated with interactive media and contextual learning, significantly enhances student engagement in the classroom. This increase in engagement positively correlates with improvements in academic achievement and their motivation to learn, marked by higher student enthusiasm and better understanding of concepts. As a research implication, it is concluded that Fun Learning is an effective and relevant learning strategy to enhance student participation and academic outcomes in elementary schools. This method not only helps address learning difficulties but also creates a fun learning environment that supports the holistic development of students, thus it is highly recommended for wider adoption in basic education.